Production of biogas from poultry manure wastewater : optimization - Wei Chun, Choo (2015)
An exaggeration increment of population has led to depletion of energy resources. One of the most effective solutions is to implement the uses of renewable energy sources. In particular, biomass, which can be further converted into biofuel, is normally derived from plants. However, it brings several drawbacks which may directly threaten the sensitive species. To alleviate these, biogas production from poultry manure wastewater was explored in the current work. Its usage to produce biogas was considered as a triumph to the concept of waste-to-wealth. The main objective of this research study was the optimization of biogas production from poultry manure wastewater by soil mixed culture. The poultry manure collected was gone through characterization and pre-treatment processes to remove excessive ammonia-N which cause inhibition to the biogas production. The optimization was analyzed by central composite design (CCD). Previous studies have screened out five processing parameters, which were agitation speed, reaction time, substrate to inoculum ratio, process system and type of substrate. Significantly, it had been identified that agitation speed and reaction time were the most crucial parameters. The best screening condition obtained from previous studies was 120 rpm agitation speed and 3 days of reaction time. Consequently, there were two factors involved in current research study, which are agitation speeds ranged from 100 rpm to 140 rpm; and reaction time ranged from 2 days to 5 days. The biogas production was collected by water displacement experimental set up. In addition, chemical oxygen demand (COD) value was determined using HACH DR5000 spectrophotometer with the aid of COD digestion reactor. Lastly, the experiment was designed and analyzed by Design Expert V7.0 software using response surface methodology (RSM). The biogas production performance was evaluated on the basis of biogas yield from initial COD and was found ranging from 0.49 to 4.37 mL/g COD. Quadratic model was well fitted (R-squared>0.80) with a confidence level higher than 95 %. For validation run, the optimum biogas production was using agitation: 120 rpm and reaction time: 3.3 days. Under this condition, 4.45 mL/g COD of biogas yield was obtained. This counted for 5.82 % error from predicted models. It is recommended to construct a pilot study of scale-up experiment for the optimization of biogas production under optimum conditions obtained from this study.